Implementation of Corporate Social Responsibility in Sharia Cooperatives in Implementing Cooperative Social Functions - Nanang Sobarna; Dady Nurpadi (LPPM Universitas Koperasi Indonesia, 2025)
This research aims to examine the implementation of Corporate Social Responsibility (CSR) in sharia cooperatives and how this supports the social function of cooperatives. CSR in sharia cooperatives plays an important role in creating sustainable added value for society, especially with the existence of sharia principles which focus on general welfare. This research uses a qualitative approach with a library study method, collecting data from various sources of accredited national journals and indexed international journals. The research results show that sharia cooperatives implement CSR through various social initiatives such as education, economic empowerment, and support for the welfare of members and communities. Effective implementation of CSR contributes to strengthening the social role of sharia cooperatives, creating a more harmonious relationship between cooperatives and the community, and increasing member loyalty. These findings provide insight that CSR based on sharia values not only fulfills social responsibility but can also strengthen the image of cooperatives and support local economic sustainability goals. Therefore, sharia cooperatives are expected to continue to develop CSR programs that are in line with sharia principles to maximize social and economic impacts for the community.